Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1574-0862.2009.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex ante analysis of the benefits of transgenic drought tolerance research on cereal crops in low‐income countries

Abstract: This article develops a framework to examine the ex ante benefits of transgenic research on drought in eight low-income countries, including the benefits to producers and consumers from farm income stabilization and the potential magnitude of private sector profits from intellectual property rights (IPRs). The framework employs country-specific agroecological-drought risk zones and considers both yield increases and yield variance reductions when estimating producer and consumer benefits from research. Benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…Recent investment in biotechnology by the Bill and Melinda Gates Foundation in Consultative Group on International Agricultural Research (CGIAR), Africa and South Asia for improving food security and poverty reduction in the less developed countries has been impressive. Kostandini et al (2009) document the ex ante impact of transgenic research for mitigating drought in rain-reliant production areas for maize, rice, and wheat in Asia and Africa.…”
Section: Other Schemes For Investing In Agricultural Technologymentioning
confidence: 99%
“…Recent investment in biotechnology by the Bill and Melinda Gates Foundation in Consultative Group on International Agricultural Research (CGIAR), Africa and South Asia for improving food security and poverty reduction in the less developed countries has been impressive. Kostandini et al (2009) document the ex ante impact of transgenic research for mitigating drought in rain-reliant production areas for maize, rice, and wheat in Asia and Africa.…”
Section: Other Schemes For Investing In Agricultural Technologymentioning
confidence: 99%
“…Regier (5) indicated that abiotic stress caused primarily by fluctuations in temperature, rainfall, salinity, sunlight, and _________________________ wind can significantly reduce yield and are already challenges faced by many farmers in Sub-Saharan Africa. Drought, which has been recognized as one of the most costly threats to agriculture accounts for an average annual production losses of 20 million metric tons of maize in tropical areas (6). Many farmers in Sub-Saharan Africa either find irrigation to be cost-prohibitive or lack the necessary groundwater resources.…”
Section: Introductionmentioning
confidence: 99%
“…Genetically Modified (GM) technology has led to the discovery of certain genes which control certain operations in the plant, allowing it to perform even under drought or heat stress (7). Empirical evidence (6,5) have shown that the use of Drought Tolerant (DT) maize varieties stabilize maize yields in drought prone ecologies and also increase land area cultivated to maize. For example, insertions of drought tolerant genes into maize have generated 10-23 percent higher yields under drought stress compared to traditional maize varieties (8 Women play significant role in contributing to the rural economy, yet they consistently have less access than men to the resources and opportunities they need to be more productive (9).…”
Section: Introductionmentioning
confidence: 99%
“…Economists predict high rates of return on investments in drought tolerant rice research and adoption of these varieties [5]. Kostandini and colleagues [5] argue that transgenic drought tolerant rice research would generate sizeable profits for technology producers (both private and public), consumers and the adoption of such cultivars would generate major benefits to farmers [6] in the affected environments in India.…”
Section: Introductionmentioning
confidence: 99%
“…Kostandini and colleagues [5] argue that transgenic drought tolerant rice research would generate sizeable profits for technology producers (both private and public), consumers and the adoption of such cultivars would generate major benefits to farmers [6] in the affected environments in India. This paper discusses impacts of adopting drought tolerance (DT) cultivars in farmers' fields in terms of yield, water use and quality attributes in China, India and Thailand.…”
Section: Introductionmentioning
confidence: 99%